2003
DOI: 10.4049/jimmunol.170.11.5793
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Reduces Autoimmune Renal Injury and Increases Survival in NZB/W F1 Mice

Abstract: Retinoic acids, a group of natural and synthetic vitamin A derivatives, have potent antiproliferative and anti-inflammatory properties. Recently, retinoic acids were reported to inhibit Th1 cytokine production. We investigated the effects of retinoic acid on lupus nephritis in a model of NZB/NZW F1 (NZB/W F1) mice. Three-month-old NZB/W F1 mice were separated into two groups: one treated with all-trans-retinoic acid (ATRA; 0.5 mg i.p., three times weekly for 7 mo) and one with saline as a control. Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 42 publications
3
71
2
Order By: Relevance
“…Disease-, sex-, and time-dependent differences were identified. Using vitamin A as a potential intervention to reduce lupus nephritis (29)(30)(31)(32), we also showed that specific changes of the gut microbiota strongly correlated with disease attenuation. Predicted metagenomes associated with murine lupus and vitamin A treatments were also described.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Disease-, sex-, and time-dependent differences were identified. Using vitamin A as a potential intervention to reduce lupus nephritis (29)(30)(31)(32), we also showed that specific changes of the gut microbiota strongly correlated with disease attenuation. Predicted metagenomes associated with murine lupus and vitamin A treatments were also described.…”
mentioning
confidence: 91%
“…Vitamin A has been shown to reduce lupus nephritis (29)(30)(31)(32). However, while orally administered vitamin A may come directly in contact with commensal bacteria in the intestinal tract during absorption, little is known about whether and how this nutrient affects gut microbiota.…”
Section: Lupus-associated Gut Microbial Composition and Diversitymentioning
confidence: 99%
“…Ig class-specific anti-DNA Abs were measured by ELISA as described previously (24). Each well of flat-bottom 96-well plates (Costar, Cambridge, MA) was coated with calf thymus DNA (Sigma-Aldrich, St. Louis, MO), dried at 37°C, and washed in isotonic PBS (pH 7.4).…”
Section: Anti-dna Absmentioning
confidence: 99%
“…It can promote anti-inflammatory Foxp3-expressing regulatory T cells and suppress proinflammatory Th17 cells (12,13). Regarding the effect of retinoic acid on autoimmune diseases, a few reports have shown the therapeutic efficacy of retinoic acid in animal models of multiple sclerosis (14) and systemic lupus erythematosus (15,16). As for the role of retinoic acid in RA, which is the prototype of autoimmune diseases, a few investigations have shown that retinoic acid had a therapeutic impact on animal models of RA (17)(18)(19)(20).…”
mentioning
confidence: 99%